Social-aware caching and forwarding for video streaming in information-centric 5G VANET - Tengfei CAO; Cuili JIANG; Zhiqiang LIU; Xiaoying WANG (Dianxin kexue)
The arrival of 5G-enabled communication technology has laid the foundation for providing high-quality video stream services in vehicular Ad Hoc network (VANET).However,current VANET still distribute video content over IP networks which design for host communication instead of content distribution.The mismatch between network function and design goals brings huge challenges for providing high quality video service.Based on the above questions,a social-aware caching and forwarding was proposed to support efficient video streaming services and the time complexity of the algorithm was O(m2).Firstly,a virtual community was constructed by analyzing the user's behaviors.Then,a fast forwarding scheme was introduced to ensure that users could discover the requested videos nearby.Finally,a community-based caching policy was proposed to optimize the in-community caching distributions.Simulation results show how the proposed strategy achieves better performance than other state-of-art solutions in terms of caching hit ratio,searching delay and control overhead.